Chlorogenic Acid-Loaded Mesoporous Silica Nanoparticles Modified with Hexa-Histidine Peptides Reduce Skin Allergies by Capturing Nickel - Tianyu Wang; Liying Yin; Zheng Ma; Yanrong Zhang (Molecules, 2022)
Nickel-induced contact dermatitis is a severe allergic reaction to objects or environments that contain nickel. Many nanomaterials have been developed to reduce skin allergies by capturing nickel, but few agents are effective and safe. In this work, mesoporous silica nanoparticles (MSN) were synthesized and decorated with hexa-histidine peptides (denoted as MSN-His6), making it a strong nickel chelator. Subsequently, a dietary polyphenol, chlorogenic acid, was loaded into the mesopores of MSN (denoted as MSN-His6@CGA), realizing the potential of its anti-inflammatory properties. In vitro and in vivo experiments revealed that the synthesized MSN-His6@CGA nanoparticles exhibited more stable and stronger chelation, better biocompatibility, and ideal allergy-relieving ability, whether for environmental metal contamination or for allergic contact dermatitis caused by prolonged nickel exposure. Thus, the application of mesoporous silica-based nanoparticles may represent an ideal approach to alleviate skin allergies by capturing nickel, which would benefit people who suffer from metal-induced contact dermatitis.